Variabilité climatique, désertification et biodiversité en afrique : s’adapter, une approche intégrée - Dorsouma Al Hamndou; Mélanie Requier-Desjardins (VertigO, 2008)
Desertification, climate change and loss of biodiversity, currently the most compelling issues in African drylands, are compromising development efforts and jeopardising the livelihoods of the poor. A growing amount of evidence is confirming the linkages between  desertification and climate change. One illustration of these linkages is that ecosystems influence the climate, and reciprocally the global climate change affects the local climate, thus exacerbating desertification, land degradation and loss of biodiversity.While the concept of climate change is an ubiquitous theme in the international meetings, desertification suffers a chronic lack of interest on the part of decision-makers. Hitherto, there are no scientific and political links through the synergy between the international environmental conventions. Climate change adaptation is crucial to addressing both issues in the context of drylands. The experience gained in combating desertification and biodiversity conservation could be an entry point for studying and understanding adaptation to climate change in Africa.This article aims to propose an integrated scientific analysis of desertification, climate change and biodiversity, in the light of the three phenomena’s definitions and manifestations in Africa’s drylands. At the institutional level, the examination of the tools and decisions taken through the multilateral conventions dedicated to climate change (UNFCCC), desertification (UNCCD) and biodiversity (UNCBD) is required.